A retrospective study of poisoning cases in Manmohan Memorial Teaching Hospital - Bajracharya, M.; Khadka, P.; Wagle, L. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Poisoning is one of the leading causes of morbidity and mortality in Nepal and also a major public health problem worldwide. It needs specific epidemiological surveillance to determine the extent and pattern of poisoning of a place, and to take preventive measures. Hence this study is aimed to explore the demographic, etiological, and clinical characteristics of poisoning cases of MMTH and to assess the effect of variables such as age, sex, and agent of poisoning frequency.Methods: A retrospective, descriptive, unicentric and semi-quantitative study was conducted in a year of 2074 at Manmohan memorial teaching hospital after institution review committee approval in customised data collection form. Data from Baishakh 2070 (April 2013) to Kartik 2074 (October 2017) were reviewed. The data was entered in SPSS 16 version for analysis.Result: Among 144 patients, poisoning was common among people from the age group of 15-25 years and 26-40 years. The females were more vulnerable than male. The male to female ratio was 1:1.4. Married females (32%) and married males (31%) were more vulnerable than unmarried ones. Poisoning incidence was found more during night (40.3%) and midnight (18.80%). 81.2% of poisoning cases were found with suicidal intention. Organophosphorous poisoning was abundant with 75 cases.Conclusion: This study reveals that OP poisoning is most common for self-harm with females and young at more risk. Therefore, awareness among youths is a must.JMMIHS.2018;4(1):55-65